Three-Point Bending Fatigue Test of TiAl6V4 Titanium Alloy at Room Temperature - Juraj Belan; Lenka Kuchariková; Eva Tillová; Mária Chalupová (Advances in Materials Science and Engineering)
A polycrystalline alpha-beta TiAl6V4 alloy in the annealed condition was used for the three-point bending fatigue test at frequency f∼100 Hz. The static preload Fstat. = −15 kN and variable dynamic force Fdyn. = −7 kN to −13.5 kN were set as fatigue test loading parameters. The fatigue life S-N curve presented the stress amplitude σa as a function of a number of cycles to fracture Nf. A limiting number of cycles to run out of 2.0 × 107 cycles were chosen for the 3-point fatigue tests of rectangular specimens. In addition, the Smith diagram was used to predict the fatigue life. The alpha lamellae width has a significant influence on fatigue life. It is assumed that the increasing width of alpha lamellae decreases fatigue life. A comparison of fatigue results with given alpha lamellae width in our material to the results of other researchers was performed. The SEM fractography was performed with an accent to reveal the initiation sites of crack at low and high load stresses and mechanism of crack propagation for the fatigue part of fracture.